The effect of guided inquiri based chemistry teaching module on students independent learning attitude: An experimental study on the characteristics of colligative solution teaching material - Leony Sanga Lamsari Purba (Pascasarjana Universitas Negeri Medan, 2020)
The purpose of this study was to work out the effect of the employment of chemistry learning modules based of colligative nature of the answer to boost of scholars independent learning attitudes. Population of this study was senior high school School PSKD 7 Depok by purposive sampling tecnique which was class XII with thirty students. Design of this study is one group pre non tes post non test group experiment. Data collection tecniques with questionnaries of 20 statement items and likert scale option. In processing data used the SPSS programs. The results of t paired test concluded that value of t count is bigger than the worth of t Table (-18.83> -23.80). Furthermore, it's also known that the importance value or post-nontest probability value (p-value) of 0,000 is smaller than 0.05 (0.000<0.05). It means there is effect of the use of chemistry learning modules based of colligative nature of the solution to improve of students independent learning attitudes. Based on the gain test to increase of students independent learning attitudes is in the high category, namely 0.82. Thus Guided Inquiri Based Chemistry Teaching Module are needed in learning nature of colligative solution. Keywords: Module; guided inquiri; learning